Attachment insecurity and strategies for regulation: when emotion triggers attention - Gonzalez, C. (2015)
Attachment-related strategies are thought to be critical for regulation and processing of emotional information. This study examined biases in selectiveattention to emotional stimuli as a function of insecure attachment. Participants searched for a single target image preceded by to-be-ignored distractersdepicting emotional images varying in valence and arousal. Results revealed that, in general, negative distracters affected accuracy levels, and that the anx-ious attached participants showed a clear interference of the emotional distracters. In contrast, the avoidant group evinced a higher control on such interfer-ence. In addition, arousal ratings to distracter images indicated superior emotional activation only for anxious attached participants. Consistent with theevolutionary-based attachment theory threat-related stimuli prompted priority attentional responses. Present findings are in line with evidence showing thedeployment of distinct strategies in insecurely attached individuals for the regulation of attention to emotional information.